Influence of the Chemical Nature of Boron‐Doped Diamond Anodes on Wastewater Treatments - Salazar-Gonzalez, R; Candia-Onfray, C; Candia-Onfray, C; Vidal-Fuentes, J (Elsevier Ltd, 2021)
This review summarizes recent advances in wastewater treatment using BDD anodes, involving different aspects of the chemical nature of the anode that are important during the oxidation of organic compounds in water. Synthesis parameters such as the proportion of diamond (sp3) and graphite (sp2), boron doping level, substrate nature and BDD surface modifications are discussed in this work. The influence of the salts dissolved in water, such as sulphate, carbonate, phosphate and chloride, during the treatment was also described. In addition, a new cycle for the oxidation of pollutants using BDD is included. © 2021 Elsevier Ltd
Keywords: Boron-doped Diamond; Wastewaters treatment; Electro-oxidation; Contaminants of emerging concern